EFFECTIVENESS OF PLAY HEALTH EDUCATION COMPARED WITH PLAY EDUCATION EARLY CHILDHOOD DEVELOPMENT IN EARLY CHILDHOOD EDUCATION AT VILLAGE KB AISYIYAH MORANGAN KARANGANOM NORTH KLATEN - Fatonah .; Sumantri .; Witriyani . (STIKES DUTAGAMA KLATEN, 2015)
Background : Play health education is game auxiliaries of edukatif about health education given to child of age early to increase health. While play education is play thing which can optimal development of child. From result of observation in PAUD KB Aisyiyah Morangan amounts to 20 childs that is age 36 months happened deviation development of according to pre questionaire skrining development. On that account researcher interests to know effectivity play health education compared to play education to development child of age early. Purpose : To know effectivity play health education compared to play education to development child of age early. Research Method : Applies sham experiment or quasy experiment. Population and sample in this research the 20 chlids in the village KB Aisyiyah Morangan Karanganom north Klaten. Sampling total divided to become 2 group, 10 child of given group of treatment and 10 childs as a group control. Analysis applies difference t-test. Result : Development score before and after done play health education with t-test that is 18,27 and play education 8,78. Conclusion : Play health education and also play education can increase development score p=0,00 ( p<0,05); CI 95% while test result t play health higher education compared to play education. Ho researcher is refused by both effective same.